Refractive lens exchange in younger and older presbyopes: comparison of complication rates, 3 months clinical and patient-reported outcomes - Schallhorn SC (Dove Medical Press, 2017)
Steven C Schallhorn,1–3 Julie M Schallhorn,1 Martina Pelouskova,3 Jan A Venter,3 Keith A Hettinger,3 Stephen J Hannan,3 David Teenan3 1Department of Ophthalmology, University of California, San Francisco, CA, USA; 2Roski Eye Institute, University of Southern California, Los Angeles, CA, USA; 3Optical Express, Glasgow UK Purpose: To compare refractive and visual outcomes, patient satisfaction, and complication rates among different age categories of patients who underwent refractive lens exchange (RLE). Methods: A stratified, simple random sample of patients matched on preoperative sphere and cylinder was selected for four age categories: 45–49 years (group A), 50–54 years (group B), 55–59 years (group C), and 60–65 years (group D). Each group contained 320 patients. All patients underwent RLE with a multifocal intraocular lens at least in one eye. Three months postoperative refractive/visual and patient-reported outcomes are presented. Results: The percentage of patients that achieved binocular uncorrected distance visual acuity 20/20 or better was 91.6% (group A), 93.8% (group B), 91.6% (group C), 88.8% (group D), P=0.16. Binocularly, 80.0% of patients in group A, 84.7% in group B, 78.9% in group C, and 77.8% in group D achieved 20/30 or better uncorrected near visual acuity (P=0.13). The proportion of eyes within 0.50 D of emmetropia was 84.4% in group A, 86.8% in group B, 85.7% in group C, and 85.8% in group D (P=0.67). There was no statistically significant difference in postoperative satisfaction, visual phenomena, dry eye symptoms, distance or near vision activities. Apart from higher rate of iritis in the age group 50–55 years, there was no statistically significant difference in postoperative complication rates. Conclusion: RLE can be safely performed in younger as well as older presbyopes. No significant difference was found in clinical or patient-reported outcomes. Keywords: refractive lens exchange, multifocal IOLs, younger/older presbyopes